Genetically increased angiotensin I-converting enzyme level and renal complications in the diabetic mouse - Huang, Wei (The National Academy of Sciences, 2001)
Diabetic nephropathy is a major risk factor for end-stage renal disease and cardiovascular diseases and has a marked genetic component. A common variant (D allele) of the angiotensin Iconverting enzyme (ACE) gene, determining higher enzyme levels, has been associated with diabetic nephropathy. To address causality underlying this association, we induced diabetes in mice having one, two, or three copies of the gene, normal blood pressure, and an enzyme level range (65–162% of wild type) comparable to that seen in humans. Twelve weeks later, the three-copy diabetic mice had increased blood pressures and overt proteinuria. Proteinuria was correlated to plasma ACE level in the three-copy diabetic mice. Thus, a modest genetic increase in ACE levels is sufficient to cause nephropathy in diabetic mice.